(untitled) (Communications in Mathematical Research, 2022)
The aim of this review is to introduce some recent results in eigenvalues problems for a class of degenerate elliptic operators with non-smooth coefficients, we present the explicit estimates of the lower bound and upper bound for its Dirichlet eigenvalues.